Getting a GRIP (getting research into practice) on movement integration in the school classroom. (4th July 2017) - Routen, Ash C.; Chalkley, Anna E.; Sherar, Lauren B.
Abstract : In adults prolonged sitting is detrimentally associated with a number of health sequela including type 2 diabetes, cardiovascular diseases and all-cause mortality, and it has been suggested these negative health consequences may not be fully protected against by participation in physical activity. Altering ubiquitous environments for children to increase their opportunities to break or reduce extended sitting is therefore of key public health interest. Emerging research shows that physical activity can be introduced into the school classroom, through short activity breaks and by integrating movement into the learning of core academic content. This may help to improve children's time on task, enjoyment of learning, and in some cases academic outcomes. This discussion paper briefly highlights some of the key research on movement integration in the classroom, discusses potential challenges and facilitators of implementation at a variety of levels (e.g. teacher, school, external stakeholder) and presents an ongoing, innovative programme (CLASS PAL) as a case study of one approach to get research on classroom movement integration into routine teaching practice.